Local Production Techniques and Sensory Evaluation of Cassava Wine - Cay, Jeyrald Jefferson; Baniaga, Gerald; Malinao, Client William (Journal of Interdisciplinary Perspectives, 2025)
This study aimed to develop a local production technique for cassava wine and evaluate its sensory acceptability across three treatments with varying cassava-to-yeast ratios: Treatment 1 (1 kg cassava, 50 g yeast), Treatment 2 (2 kg cassava, 50 g yeast), and Treatment 3 (3 kg cassava, 50 g yeast). Specifically, it assessed aroma, appearance, taste, texture, and respondents’ likelihood of consuming cassava wine compared to other options. A quantitative approach integrating descriptive and experimental methods was employed. Sensory evaluations, conducted using a hedonic scale, revealed distinct acceptability levels among the treatments. Treatment 1 received moderate ratings for appearance (40%) and high ratings for aroma (30%), with most respondents describing its taste as sweet with a mild alcoholic note. Treatment 2 garnered mixed feedback, with 50% moderately liking the appearance and 40% slightly liking the flavor. Treatment 3 achieved the highest overall acceptability, with 50% highly rating its appearance and 40% moderately appreciating its taste. Regarding consumption preference, 40% of respondents indicated a willingness to consume Treatment 3 regularly, a preference comparable to rice wine. The study highlights the potential of cassava wine, particularly the variant produced with 3 kg of cassava, as a viable alternative in local markets. Enhancing fermentation techniques, increasing consumer awareness, and promoting cassava wine could improve its acceptance and commercial viability.